Influence of preharvest nano calcium applications on postharvest of sweet pepper (Capsicum annum) - FARIBA AMINI; LADAN BAYAT; SHIMA HOSSEINKHANI (Nusantara Bioscience, 2016)
Abstract. Amini F, Bayat L, Hosseinkhani S. 2016. Influence of preharvest nano calcium applications on postharvest of sweet pepper (Capsicum annum). Nusantara Bioscience 8: 215-220. The effect of preharvest nano calcium treatment on the quality, physicochemical parameters and antioxidative enzyme activities of sweet pepper fruits were evaluated. For this purpose, sweet pepper plants treated with three concentrations (0, 4 and 8 g/L) of nano calcium in five steps (50, 60, 70, 80 and 90 days after pepper planting). 100 days after pepper planting, fruits were harvested and packaged in plastic bags and stored at 20±3 0C, then total soluble solids, pH, weight loss, carotenoids, electrolyte leakage, lipid peroxidation, titrable acidity, ascorbic acid, chlorophyll, calcium, protein and the activities of total antioxidant enzymes, catalase, and guaiacol peroxidase were evaluated at 0, 7, 14 and 21 days of storage period. Nano calcium treated fruits had lower levels of total soluble solids, pH, weight loss, carotenoids, electrolyte leakage, lipid peroxidation and higher levels of titrable acidity, ascorbic acid, chlorophyll, calcium and protein compared to the control plants. The increase percentage of titrable acidity, ascorbic acid, chlorophyll a, chlorophyll b, total chlorophylls, calcium and protein contents in plants treated with 4 g/L nano calcium and 21 days storage period were calculated 68.86%, 41.89%, 81.17%, 78.57%, 80.81%, 21.46% and 83.30% respectively. The maximum activities of total antioxidant enzymes, catalase and guailcol peroxidase were observed in 21 days control plants that application of nano calcium decreased these antioxidant activities. In most parameters 4 g/L concentration was more effective. Therefore, commercial application of preharvest nano calcium (4 g/L) can be considered for the maintenance of quality of sweet peppers during storage and marketing.